Global trends of peripheral immune tolerance research: a bibliometric and visualization analysis - Kong, Shixiao; Lin, Chen; Shen, Yuting; Chen, Jun (Frontiers in Immunology, 2026)
BackgroundPeripheral immune tolerance is a key mechanism for maintaining immune homeostasis and preventing autoimmune responses. Although numerous studies have explored its molecular and cellular basis, a comprehensive and systematic overview of the field is still lacking. This study aims to elucidate the global research landscape of peripheral immune tolerance through bibliometric analysis.MethodsPublications related to peripheral immune tolerance from 1989 to 2025 were retrieved from the Web of Science Core Collection and Scopus databases. After removing duplicates, a total of 3,098 papers were included. CiteSpace, VOSviewer, RStudio Biblioshiny, and OriginPro were used for systematic analysis, allowing effective identification of research trends and emerging topics.ResultsSince the 1990s, the annual number of publications on peripheral immune tolerance has steadily increased, peaking in 2008 before showing a slight decline. High-frequency keywords included autoimmunity, tolerance, and regulatory T cells. The United States, Germany, China, and Japan were the leading contributors, with Harvard University ranking first in both publication volume and citation frequency. Highly cited landmark papers by Sakaguchi, Freeman, and Curiel laid the theoretical foundation for the field. The Journal of Immunology had the highest publication count, while Nature Immunology showed the greatest impact.ConclusionThis study provides the first comprehensive bibliometric analysis of global research on peripheral immune tolerance, revealing the evolution of research themes over the past three decades and forecasting future trends. The findings offer valuable data support and insights for advancing research in this field.Systematic review registration: